An Experimental Approach to Vibro-Acoustic Study of Beam-Type Structures - TORRES-ROMERO, Jeniffer; CARDENAS, William; CARBAJO, Jesus; SEGOVIA EULOGIO, Enrique G.; RAMIS-SORIANO, Jaime (Archives of Acoustics, 2018)
In this paper an alternative procedure to vibro-acoustics study of beam-type structures is presented. With this procedure, it is possible to determine the resonant modes, the bending wave propagation velocity through the study of the radiated acoustic field and their temporal evolution in the frequency range selected. As regards the purely experimental aspect, it is worth noting that the exciter device is an actuator similar to is the one employed in distributed modes loudspeakers; the test signal used is a pseudo random sequence, in particular, an MLS (Maximum length Sequence), facilitates post processing. The study case was applied to two beam-type structures made of a sandstone material called Bateig. The experimental results of the modal response and the bending propagation velocity are compared with well-established analytical solution: Euler-Bernoulli and Timoshenko models, and numerical models: Finite Element Method-FEM, showing a good agreement.